(untitled) (Journal of Global Arts Studies, 2024)
Background: In the context of globalization and digitization, the forms and methods of cultural communication are undergoing significant changes. Objective: This paper explores the impact and opportunities of this transformation on traditional cultural dissemination, with an in-depth analysisfocusing on South Korea and China. Methods: Firstly, it analyzes how South Korea successfully promotes its culture through modern media platforms and the cultural industry, with particular emphasis on its successful practices through television dramas and K-pop idol groups. Subsequently, it discusses the challenges faced by China in traditional cultural dissemination, proposing some strategies that may draw lessons from South Korea’s successful experiences and introducing the new role of social media platforms in cross-cultural communication. Results: China needs to utilize modern media and the cultural industry, adopting more diverse and innovative ways to disseminate traditional culture, in order to enhance the vitality and global influence of traditional culture. Conclusion: Finally, the importance of protecting and inheriting local culture, especially in the context of globalization and digitization, is discussed along with the challenges and coping strategies. This paper aims to provide new perspectives and insights to help better understand and respond to the new situation of cultural communication today